A 3D interconnected NH4Fe0.6V2.4O7.4@C nanocomposite with superior sodium storage properties. Issue 15 (3rd April 2018) - Xiong, Zhenmin; Chen, Lei; Zhao, Long; Zhao, Yanming; Feng, Jingjie; Huang, Chun mao; Dong, Youzhong; Zhang, Hui; Wang, Yang; Kuang, Quan; Fan, Qinghua; Liu, Shenghong; et al.
Abstract : A novel 3D interconnected NH4 Fe0.6 V2.4 O7.4 @C nanocomposite was in situ synthesized through a facile hydrothermal reaction at low temperature (98 °C), and its electrochemical performance as a cathode for sodium-ion batteries (SIBs) was investigated for the first time. Abstract : A novel 3D interconnected NH4 Fe0.6 V2.4 O7.4 @C nanocomposite was in situ synthesized through a facile hydrothermal reaction at low temperature (98 °C), and its electrochemical performance as a cathode for sodium-ion batteries (SIBs) was investigated for the first time. Under the intercalation of Fe 3+ and carbon-coating, as-prepared samples turned to 3D interconnected structures, which were composed of NH4 Fe0.6 V2.4 O7.4 nanoparticles and carbon chains. The 3D interconnected NH4 Fe0.6 V2.4 O7.4 @0.5 wt%C nanocomposite exhibits a high discharge specific capacity of 306 mA h g −1 at a current density of 20 mA g −1 and a high-rate capacity of 130 mA h g −1 at 0.4 A g −1 . The results of EIS and ex situ SEM indicated that the 3D interconnected NH4 Fe0.6 V2.4 O7.4 @0.5 wt%C nanocomposite possesses good electrical conductivity and structural stability. The ex situ XRD results suggest that NH4 Fe0.6 V2.4 O7.4 @0.5 wt%C undergoes a reversible insertion/de-insertion mechanism during a charge/discharge process. Our work demonstrates that the 3D interconnected NH4 Fe0.6 V2.4 O7.4 @C nanocomposite material could be considered as a potential cathode for sodium ion batteries.